An automated approach for the aerodynamic design of close-coupled propulsion/airframe configurations - Matesanz García, Jesús; Christie, Robert; Tejero, Fernando; MacManus, David G.; Heidebrecht, Alexander (Council of European Aerospace Societies (CEAS), 2020)
Reducing aircraft emissions is a key element in mitigating the environmental impact of aviation. Within this context, different novel aircraft propulsion configurations have been proposed. A common feature of many of these novel configurations is the closer integration of the propulsive system and the aircraft airframe with an expected increase of the aerodynamic coupling. Therefore, is necessary to assess the performance of the aerodynamic installation of the propulsive system of these configurations with a systematic approach. A systematic and automated methodology for the design and performance evaluation of embedded propulsion systems is defined. This methodology is demonstrated with a Boundary Layer Ingestion propulsive fuselage concept. This approach covers the geometry design of the selected configuration, an automatic aerodynamic numerical computation and a novel performance evaluation for the design. A Design Space Exploration was performed to characterize the relative importance of the individual parameters of the geometry and their correlation with the key performance metrics. Finally, a multi-objective optimization was carried to demonstrate the capabilities of this approach.
Keywords: CFD; Design Space Exploration; multi-objective optimizations; genetic algorithm; Novel aircraft configurations; boundary layer ingestion; propulsive fuselage; aerodynamic performance; Class Shape Transformations